PENYULUHAN HUKUM PERLINDUNGAN PEKERJA MIGRAN INDONESIA DI DESA MATAWAI ATU - Maria Fransiska Owa Da Santo; Ernesta Uba Wohon; Filemon Fridolino Ngebos; Stefanus Don Rade; Genoveva Sumanti (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
Matawai Atu Village in Umalulu District, East Sumba Regency, is known for its high rate of labor migration abroad, especially through non-procedural or illegal channels. The community faces a lack of awareness about the legal processes for the placement of Indonesian Migrant Workers (IMWs) and limited access to information regarding their legal protection. This community service project aimed to improve public understanding of proper migration procedures and raise awareness of the legal and social risks associated with non-procedural migration. The method used was legal education through interactive lectures and group discussions, supported by the distribution of educational materials. The activity was held on May 28, 2025, at the Matawai Atu Village Office and involved active participation from local residents. Qualitative data were gathered through observations and questions raised during the sessions. The materials covered key topics such as the definition and rights of IMWs, legal frameworks, the role of BP2MI, and the dangers of undocumented migration. The results indicated a significant increase in participants’ understanding of the importance of legal procedures and greater awareness of institutional protection. This activity also encouraged the involvement of local leaders in preventing illegal labor migration. Continued efforts are needed to ensure sustainable legal awareness among communities vulnerable to unsafe migration practices.